Coldwater capture fishery in the Ganga headwaters having operational hydropower projects: A failing co-existence - Nautiyal, Prakash; Kumar, Sandeep; Sharma, Neetika; Chauhan, Kavita; Kala, Kavita (Journal of the Inland Fisheries Society of India, 2020)
Not all fisher have or can become farmers. Many of them hence depend on the rivers for thei livelihood. The uplands of the Ganga basin by virtue of mountain terrain give access to the rivers at limited places only. Hydropower development is gradually changing the face of rivers. Here we examine ecological changes undergone by the Alaknanda and Bhagirathi rivers through decades of hydropower development. We also demonstrate the changes undergone by the capture fishery, in terms of total landings and their composition over this period. Snow trout which forms major fishery in all glacier fed rivers of the Ganga basin does not any more figure in the fishery of Tehri reservoir that has been invaded by the common carp. No doubt, the reservoir is providing a good catch of mahseer, but how long it can be sustained, is a big question in the face of current form of fishery (no limit on mesh size). The reservoirs have been projected as a means to enhance fishery, but only if the exotic carps (common, grass, silver) are introduced. Deep water column of the reservoir is not suitable for snow trout that needs high oxygenated waters, possible only in ariver. Therefore, in the uplands there is a failing co-existence and is now a more like a living-in relationship, with indigenous species living till they cease to exist as they don’t have the facility to go elsewhere unlike human society that can walk - in and out as and when they like. Keywords Bhagirathi, Alaknanda, Dams, Tehri,Srinagar, Current velocity, Macroinvertebrate community, Coldwater fishery.